2012
DOI: 10.1002/cmdc.201100512
|View full text |Cite
|
Sign up to set email alerts
|

Pentacycloundecane‐diol‐Based HIV‐1 Protease Inhibitors: Biological Screening, 2D NMR, and Molecular Simulation Studies

Abstract: Novel compounds incorporating a pentacycloundecane (PCU) diol moiety were designed, synthesized, and evaluated as inhibitors of the wild-type C-South African (C-SA) HIV-1 protease. Seven compounds are reported herein, three of which displayed IC(50) values in the 0.5-0.6 μM range. The cytotoxicity of PCU cage peptides toward human MT-4 cells appears to be several orders of magnitude less toxic than the current antiviral medications ritonavir and lopinavir. NMR studies based on the observed through-space (1)H,(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…As the X‐ray crystal structure of C‐SA HIV PR was not yet resolved, we previously reported the use of a computationally generated enzyme model. The modeling scenario and validation of the created C‐SA HIV PR model have been reported in our previous work . Even though the X‐ray crystal structure of the C‐SA HIV PR (PDB code: 3U71) was recently published , we believe that the use of the modeled enzyme system would still be more appropriate for several reasons.…”
Section: Methodsmentioning
confidence: 95%
“…As the X‐ray crystal structure of C‐SA HIV PR was not yet resolved, we previously reported the use of a computationally generated enzyme model. The modeling scenario and validation of the created C‐SA HIV PR model have been reported in our previous work . Even though the X‐ray crystal structure of the C‐SA HIV PR (PDB code: 3U71) was recently published , we believe that the use of the modeled enzyme system would still be more appropriate for several reasons.…”
Section: Methodsmentioning
confidence: 95%
“…Ribbon representation of overlay of modelled I36T↑T protease (brown) and wild‐type HIV‐1 subtype C (blue) previously reported (). The amino acid mutations (green), the amino acid insertion (red) and the catalytic Asp (yellow) are highlighted as spheres.…”
mentioning
confidence: 61%
“…The Leap module of amber12 package was used to add missing protons to the protein. Particularly, the protonation state of the catalytic Asp25 residue has been examined in our previous work and other studies, according to our previous investigations, showed that there is no significant difference between the binding free energy results for the monoprotonated and unprotonated states; therefore, the Asp25 residues in this study were left in the unprotonated state . The Amber force field for bioorganic systems (ff03.r1) was used in describing the parameters of the protein, while the inhibitors were described by GAFF parameters as implemented on amber12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until late 2012, the X‐ray crystal structure of the C‐SA PR was unavailable, limiting information on how drugs interact with this enzyme. A computational model for the C‐SA PR based on its protein sequence was developed [Mosebi et al., ] and used in previous studies [Makatini et al., 2011a, b, ; Honarparvar et al., ; Karpoormath et al., ]. Recently, the first X‐ray crystal structure of C‐SA HIV PR was reported [Naicker et al., ], allowing comparison of the unique structural and dynamic features of the C‐SA PR enzyme with subtype B.…”
Section: Introductionmentioning
confidence: 99%